Mapping Ambient Temperature and Leptospirosis Cases: A Spatial Approach in Central Java - Dewi, Indra; Saputra, Yoerdy Agusmal (Open Access Health Scientific Journal, 2025)
Background: Leptospirosis remains a global public health concern as a neglected and re-emerging tropical disease with substantial morbidity and mortality. This study investigates the association between ambient temperature and leptospirosis cases in Central Java to elucidate disease transmission patterns.Methods: A quantitative approach was employed, integrating geographic information system (GIS) analysis with descriptive spatial methods. The study examined leptospirosis cases and ambient temperature trends from 2018 to 2022 across all districts and cities within Central Java Province.Results: These findings underscore the necessity of incorporating temperature-based risk assessment into public health strategies, particularly through the implementation of spatially driven monitoring systems to identify high-risk regions and mitigate leptospirosis transmission in temperature-prone areas. Spatial analysis revealed that areas characterized by high to moderate minimum, maximum, and average temperatures, such as Banyumas, Demak, and Semarang City, exhibited a greater case of leptospirosis compared to areas with lower temperatures.Conclusion: This study showed that areas with high and medium minimum, maximum, and average temperatures, such as Banyumas, Demak, and Semarang City, tended to have higher leptospirosis cases than areas with low minimum temperatures, highlighting the need for spatial-based monitoring systems to detect high-risk areas, particularly those with warm ambient temperatures.